COMPARISON ANALYSIS ON AWL OF THE ARTICLES IN INDONESIAN JOURNAL OF APPLIED LINGUISTICS AND OXFORD UNIVERSITY PRESS OF APPLIED LINGUISTICS - Mahsyurotun Nikmah (Department of Master of Linguistic, Universitas Airlangga, 2018)
This study focus on comparing the utilization of Academic Word List (AWL) from the local and International journal article. The articles that used in this study must meet two criteria. First, the articles should have open access articles. Eventually it is found the journal articles from Indonesian Journal of Applied Linguistics (IJAL) and Oxford University Press of Applied Linguistics (OUP) that provide the open access articles. Second, the articles should have the newest issues that have been published in the last two years. There are fifteen articles that have been chosen, and it found 507 academic word families of AWL from IJAL and 535 academic word of OUP. The Type Token Ratio (TTR) of AWL from IJAL is about 0,13%, while the Type Token Ratio of AWL from OUP is about 0,09%. The articles of IJAL have the percentage of AWL about 10,22% but the OUP articles shows 11,41%. There are 68 different of academic words from the articles of IJAL and OUP, the 20 words belong to IJAL and the other 48 words belong to OUP. Those differences word are then occupied into the Sublist AWL, it is found that the 20 AWL of IJAL journal only fill the sublist 9 and 10, while the 48 other AWL of OUP journal are categorized into sublist 2 up to sublist 10. It can be concluded that both of the journal articles of IJAL and OUP are categorized as academic journal although it is in different side.